Direct Formation of Tethered Ru(II) Catalysts Using Arene Exchange - Soni, Rina (American Chemical Society, 2013)
[Image: see text] An ‘arene exchange’ approach has been successfully applied for the first time to the synthesis of Ru(II)-based ‘tethered’ reduction catalysts directly from their ligands in one step. This provides an alternative method for the formation of known complexes, and a route to a series of novel complexes. The novel complexes are highly active in both asymmetric transfer and pressure hydrogenation of ketones.